BLISS: Shining a light on lignification in plants. (3rd August 2017) - Simon, Clémence; Lion, Cedric; Huss, Brigitte; Blervacq, Anne-Sophie; Spriet, Corentin; Guérardel, Yann; Biot, Christophe; Hawkins, Simon
ABSTRACT: Lignin is a polyphenolic polymer of the plant cell wall formed by the oxidative polymerization of 3 main monomers called monolignols that give rise to the lignin H-, G- and S-units. Together with cellulose and hemicelluloses, lignin is a major component of plant biomass that is widely exploited by humans in numerous industrial processes. Despite recent advances in our understanding of monolignol biosynthesis, our current understanding of the spatio-temporal regulation of their transport and polymerization is more limited. In a recent publication, we have reported the development of an original Bioorthogonal Labeling Imaging Sequential Strategy (BLISS ) that allows us to visualize the simultaneous incorporation dynamics of H and G monolignol reporters into lignifying cell walls of the flax stem. 11 Here, we extend the application of this strategy to other plant organs such as roots and rapidly discuss some of the contributions and perspectives of this new technique for improving our understanding of the lignification process in plants.